Oral and intramuscular application of cyanogenic glycoside amygdalin did not induce changes in haematological profile of male rabbits - Katarína Zbyňovská (Potravinarstvo, 2017)
Amygdalin is a cyanogenic glycoside initially obtained from the seeds of bitter almonds. It is composed of one molecule of benzaldehyde, two molecules of glucose and one molecule of hydrocyanic acid. Various ways of amygdalin application play a different role in recipient organism. Intravenous infusion of amygdalin produced neither cyanidemia nor signs of toxicity, but oral administration resulted in significant blood cyanide levels. The present in vivo study was designed to reveal whether amygdalin is able to cause changes in the haematological profile and thus alter the physiological functions, using rabbits as a biological model. Adult male rabbits (n = 20) were randomly divided into five groups: the control group without any amygdalin administration, two experimental groups received a daily intramuscular injection of amygdalin at a dose 0.6 and 3.0 mg.kg-1 b.w. and other two groups were fed by crushed apricot seeds at dose 60 and 300 mg. kg-1 b.w., mixed with commercial feed over the period of 14 days. After two weeks, haematological parameters in whole blood were analysed (WBC - total white blood cell count, LYM - lymphocytes count, MID - medium size cell count, GRA - granulocytes count, RBC - red blood cell count, HGB - haemoglobin, HCT - haematocrit, MCV - mean corpuscular volume, MCH - mean corpuscular hemoglobin, MCHC - mean corpuscular hemoglobin concentration, RDWc - red cell distribution width, PLT - platelet count, PCT - platelet percentage, MPV - mean platelet volume, PDWc - platelet distribution width) using haematology analyser Abacus junior VET. Our findings indicate that intramuscular and oral application of amygdalin for two weeks did not significantly affect the haematology parameters in experimental animals. In this study, no obvious beneficial or negative effects of amygdalin administration on the blood of male rabbits were observed.